Modeling economic growth in contemporary Russia - Sergi, Bruno S.,
Russia is one of the world's largest growing economies. With this exciting new growth and development, there is a wealth of knowledge to be discovered from the strategies and models being used and created throughout Russia's economy.Modeling Economic Growth in Contemporary Russia portrays and sets pieces of Russia's growth strategies to produce an extraordinary record of economic analysis. A leading expert in emerging markets, editor Bruno S. Sergi and a cast of experienced Russian academics offer a wealth of questions and critical examples on Russia that are delivered through a sound framework and provide unique knowledgeable support and interdisciplinary research about modeling a sound growth strategy for Russia. Through various chapters on financial development and economic growth, Sergi explores the fascinating landscape of Russia's economy, including chapters on green investment; education and inclusive development; sustainability; smart cities; international cooperation; and innovation-based growth.For anyone interested in international economics, or students of emerging economies and markets, this is a fundamental study of an area that has never before been studied in such depth.